Forming of spontaneity and creativity during playback theater activities - Trofimov, Andrii Yu.; Yurchynska, Hanna K.; Lovochkina, Antonina M.; Pohorilska, Nataliia I.; Ananova, Ivanna V.; Drobot, Olga V. (Linguistics and Culture Review, 2021)
Finding the solution of many problems requires from person an ability of quick unconscious perception. Between spontaneity and creativity, there are both positive and negative relationships. In accordance with the authors’ forming program, the participants were equated with Playback actors with only difference that the actors aim to improve their skills while the participants develop their spontaneity. The authors have built the forming program which contained a set of training and developmental exercises and games aimed at developing spontaneity, attention and creative thinking. Six interconnected blocks of the forming program structure were characterized (Introduction; The development of spontaneity through creativity; The development of spontaneity through tolerance to uncertainty; The development of spontaneity through autonomy; Generalization and combination; Summing up). Its effectiveness was analyzed with help of an initial and final survey of participants. During the study, the participants’ level of spontaneity increased.